Educational data mining current research and open questions - Rodrogo, Ma. Mercedes T. (Philippine computing journal)
Educational data mining (EDM) refers to the application of statistical and machine learning methods to educational data in order to achieve one of four typical ends; improvement of student models, improvement of subject matter domain structures, studying pedagogical support...